Aggregate earnings-returns relation: insights from REITs - Ijaz Ali (Cogent Business & Management, 2022)
Prior research generally reports a positive relationship between firm-level accounting earnings surprises and contemporaneous stock prices, indicating that accounting earnings carry value-relevant information. Recent studies, however, show that investors respond negatively to unexpected changes in aggregate earnings. These findings present a puzzle for researchers. We examine the earnings/return association at the firm- and aggregate-level using a dataset of all publicly listed US REITs from 1998 to 2018. The analysis aims to know whether the negative association between the two variables exists in industry-level data, specifically REITs. We fail to find an inverse relationship between aggregate earnings changes and concurrent stock returns in REITs; yet, our data support the notion that aggregate level accounting income is relatively more predictable than firm-level income. Our results indicate that the previously observed negative aggregate earnings/return relation seems to be triggered by information transfer across various industrial sectors.
Keywords: 650; information asymmetry; aggregate earnings; earnings predictability; REITs; stock returns